Consequences of the COVID-19 pandemic on the diagnosis and treatment of gastric cancer in referral centers in Italy. Issue 1 (February 2023) - Solaini, Leonardo; Bencivenga, Maria; Rosa, Fausto; D'ignazio, Alessia; Marino, Elisabetta; Ministrini, Silvia; Sofia, Silvia; Sacco, Michele; Mura, Gianni; Rausa, Emanuele; Prizio, Marco De; Graziosi, Luigina; et al.
Background: The coronavirus pandemic had a major impact in Italy. The Italian health system's re-organization to face the emergency may have led to significant consequences especially in the diagnosis and treatment of malignancies. This study aimed to assess the impact of the pandemic in the diagnosis and treatment of gastric cancer in nine Gruppo Italiano RIcerca Cancro Gastrico (GIRCG) centers. Methods: All patients assessed for gastric adenocarcinoma at nine GIRCG centers between January 2019 and November 2020 were included. Patients were grouped according to the date of "patient 1's" diagnosis in Italy: preCOVID versus COVID. Clinico-pathological and outcome differences between the two groups were analyzed. Results: A total of 632 patients were included in the analysis (205 in the COVID group). The cT4 weighted ratios were higher in 2020 from April to September, with the greatest differences in May, August and September. The cM+ weighted ratio was significantly higher in July 2020. The mean number of gastrectomies had the greatest reduction in March and May 2020 compared with 2019. The median times from diagnosis to chemotherapy, to complete diagnostic work-up or to operation were longer in 2019. The median time from the end of chemotherapy to surgery was 17 days longer in the preCOVID group. Conclusions: A greater number of advanced or metastatic cases were diagnosed after the spread of SARS-CoV-2 infection, especially after the "full lockdown" periods. During the pandemic, once gastric cancer patients were referred to one of the centers, a shorter time to complete the diagnostic work-up or to address them to the best treatment option was required.